Histological evaluation of the effect of topical application of Curcumin powder and essential oil on skin wound healing - Muhammad, Nidhal H; Ghani, Ban A (Journal of Baghdad College of Dentistry, 2015)
Background: Herbal medicine can be called one of the branches of medicine in various forms. Turmericcurcumin has proved its efficiencies a coloring, flavoring agent and has been traditionally used in medicine, exhibiting remarkable anti-inflammatory and antioxidant properties. The varied biological properties of curcumin and lack of toxicity even when administered at higher doses makes it attractive to explore its use in various disorders like diseases of skin. It is good potential agent for wound healing.Materials and methods: Sixty four new Zealand rabbits were used in this study ,they were divided into four groups,each group was subdivided as follows:Experimental groups(8 rabbits) right facial side of animals for essential oil application and left facial side animals for curcumin powder application,8animals as control group(right facial sides) .Histological assessment regarding the count of inflammatory cells was performedon all studied samples for the healing intervals (3, 7, 10, and14 days).Results: Histological findings of the study showed that re-epithelialization, wound contraction were accelerated after topical application of curcumin material especially the essential oil at wound site.Conclusion: Topical application of curcumin essential oil was significantly effective in skin wound healing as compared to curcumin powder.